The pattern of medical errors and litigation against doctors in Saudi Arabia - Jamal S AlJarallah; Norah AlRowaiss (Wolters Kluwer Medknow Publications, 2013)
Background: Adverse events are frequent in clinical practice, but only a few studies in Saudi Arabia have addressed them. The current study was designed to review the lawsuits against healthcare professionals by analyzing records of the cases dealt with by the Medico-legal Committees (MLC) in various provinces in Saudi Arabia, in order to determine the pattern of medical errors and litigations in the country. Materials and Methods: A pre-designed data sheet was used to collect data from the records of the Medical Violation Committee (MVC) and the Medical Jurisprudence Committee (MJC). The data sheets consisted of information on details of the cases, details on where the error had occurred, and details of the errors. Results: The review of records revealed 642 cases, most of which were from hospitals run by the Ministry of Health (MOH). The operating room was where most of the errors (20.4%) had occurred, followed by the emergency room (18.1%). Surgery was at the top of the specialties (25.1%). Most of the deaths occurred in surgery and obstetrics (about 25% for each), followed by other medical specialties (17%). About half of the lawsuit cases studied (46.5%) involved patients belonging to a relatively young age group (20-50 years). Conclusion: Most of the medical error litigations involved surgeons and obstetricians especially in MOH hospitals. The process of litigations and documentation need to be improved, and access to the records for research and education need to be made easier. In addition, there is a need for more prospective field studies.